THE EFFECT OF SOCIAL MEDIA ON THE SECOND YEAR STUDENT’S ACADEMIC ACHIEVEMENT IN STKIP MUHAMMADIYAH MUARA BUNGO - renda Lestari (Journal Of Language Education and Development (JLed), 2018)
The aim of the study was to analyze the impact of social media on the student’s academic achievement. The survey research method was used. Subjects were drawn from the second year students of Elementary Teacher Education Department in STKIP Muhammadiyah Muara Bungo The researcher adopted Kendall’s coefficient of concordance and factor analysis as analytical tools for the study. A survey design provides a quantitative description of the population that is sampled through the data collection process (Frankel and Wallen, 1995). The study also employed the questionnaire as the data collection instrument for the study. The Statistical Package for Social Sciences (SPSS) was used to analyze the data collected. The descriptive analysis tools in the SPSS were employed to develop tables and frequencies which were constructively analyzed. The result revealed that majority of respondents used whatsapp and facebook to find new friends and application for communication. Furthermore, majority of respondents experienced negative effects such as late submission of assignment, less study time and poor academic achievement due to the heavy participation on social media networks. Therefore, there were cases where others experienced improvement in their reading skill as a result of participation on social media networks. Also respondents shared ideas, discussed and shared examination among them on social media network. The study recommended the strict enforcement of STKIP Muhammadiyah Muara Bungo rule on electronic devices usage in campus, promotion of social media usage for academic purpose and counseling for addicted students